2012
DOI: 10.1111/j.1747-0080.2012.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor knowledge and dietary practices related to iodine in breastfeeding mothers a year after introduction of mandatory fortification

Abstract: Aim:  Public health has refocused attention on low iodine status of vulnerable groups. The purpose of this research was to identify knowledge and dietary practices related to iodine nutrition in breastfeeding women in the Illawarra region following introduction of the mandatory iodine fortification programme. Methods:  A cross‐sectional study was undertaken at four early childhood centres. Sixty mothers in their first six months of breastfeeding completed a short knowledge questionnaire, an iodine‐specific foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…Inadequate iodine supplementation has also been found in other Australian studies of pregnant and breastfeeding women . Similarly, poor knowledge about iodine in pregnancy and dietary sources of iodine has been previously demonstrated in Australian pregnant and lactating women . This study showed that most pregnant women were aware of the importance of folate compared with iodine.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Inadequate iodine supplementation has also been found in other Australian studies of pregnant and breastfeeding women . Similarly, poor knowledge about iodine in pregnancy and dietary sources of iodine has been previously demonstrated in Australian pregnant and lactating women . This study showed that most pregnant women were aware of the importance of folate compared with iodine.…”
Section: Discussionsupporting
confidence: 76%
“…A review by Charlton et al . also found that pregnant and lactating women were better informed about folate and other dietary issues related to pregnancy than iodine . Previous studies indicate that many Australian pregnant and lactating women feel that they had not received sufficient information regarding iodine for their pregnancy …”
Section: Discussionmentioning
confidence: 99%
“…As well as fortified bread, we identified that other major sources of iodine for the total Australian population in 2011–2013 included milk products and dishes (26%), non-alcoholic beverages (15%) and cereal based products and dishes (12%). Despite being rich in iodine, fish and seafood contributed only minimally to total iodine intake due to low reported consumption, as has been reported by other studies [23,34]. Previous studies in pregnant Australian women identified that dairy foods were a major contributor to total iodine intake (57%–62%), followed by bread and cereals (19%–21%) with minor contributions from fish and seafood (3%–8%) [14,23].…”
Section: Discussionmentioning
confidence: 53%
“…Other individual factors have been consistently shown to be associated with eating behaviours including nutrition knowledge and self‐efficacy 19 . Research by Axford et al 20 . highlights the importance of nutrition knowledge in the area of iodine.…”
Section: Potential Determinants Of Food and Nutrition‐related Behavioursmentioning
confidence: 99%
“…18 Other individual factors have been consistently shown to be associated with eating behaviours including nutrition knowledge and self-efficacy. 19 Research by Axford et al 20 highlights the importance of nutrition knowledge in the area of iodine. They demonstrated that even among a well-educated sample of breastfeeding women, knowledge relating to iodine, such as its importance to health, good sources of iodine and the need for supplements during lactation, was poor.…”
Section: Potential Determinants Of Food and Nutrition-related Behavioursmentioning
confidence: 99%